Endoscopic management of bile leaks after liver transplantation: An analysis of two high‐volume transplant centers. Issue 1 (1st February 2018) - Sendino, Oriol; Fernández‐Simon, Alejandro; Law, Ryan; Abu Dayyeh, Barham; Leise, Michael; Chavez‐Rivera, Karina; Cordova, Henry; Colmenero, Jordi; Crespo, Gonzalo; Rodriguez de Miguel, Cristina; Fondevila, Constantino; Llach, Josep; et al.
Abstract : Background: Bile leak after liver transplantation (LT) is commonly treated with endoscopic retrograde cholangiopancreatography (ERCP); however, there are limited data regarding the optimal treatment strategy. Objective: We aimed to examine the role of ERCP in LT recipients with bile leaks at two large institutions. Methods: We reviewed all ERCPs performed in LT recipients with bile leak and duct‐to‐duct biliary anastomosis at two high‐volume transplant centers. Results: Eighty patients were included. Forty‐seven (59%) patients underwent ERCP with plastic stent placement (with or without sphincterotomy) and 33 patients (41%) underwent sphincterotomy alone. Complete resolution was obtained in 94% of the stent group vs. 58% of the sphincterotomy group ( p  < 0.01). There was no difference in three‐month survival among both groups. Percutaneous transhepatic therapy and surgery were required in 4% and 6% in the stent group vs. 12% and 42% in the sphincterotomy group, respectively ( p  = 0.22 and p  < 0.001). The only predictive factor of bile leak resolution was stent placement. Conclusion: ERCP with plastic stent placement is highly successful and more effective than sphincterotomy alone for post‐LT bile leak treatment. These results indicate that ERCP and plastic stent placement should be considered the standard of care for the treatment of bile leaks in LT.